Team work : forging links between honesty, accountability and success - McLean, Ray J., 1959-; McNicol, Adam (Port Melbourne : Leading Teams Australia Pty Limited, 2015)
There are no shortcuts to good leadership and effective teamwork, but diagnosing the problem is often the first step to improving team performance. Using candid case studies from teams who have used the Performance Improvement Program, Leading Teams' founder and co-director Ray McLean goes back to basics, explaining the principles of empowerment and responsibility and how they link to success. For twenty years, Leading Teams has successfully implemented its no-nonsense program in a wide variety of team environments from Hawthorn Football Club to Jim's Test and Tag, Nillumbik Shire Council to Quicksilver and more than one hundred schools. If you work as part of a team and know that there's room for improvement, this book will get you thinking about how to move forward.
First published in 2010.
Includes bibliographical references.
Keywords: Leadership; Organizational behavior; Psychology, Industrial; Teams in the workplace; Teamwork (Sports); Australian